The Dual Effect of Board Gender and Female Director Independence on Firm Performance in Malaysia - Siti Fatimah Mohd Jamaluddin; Aliana Shazma Amir; Zulaikha Rabitah Zaidi (Universitas Medan Area, 2025)
Corporate governance plays an increasingly important role in shaping firm performance, particularly in emerging markets such as Malaysia. This study examines the impact of corporate governance factors, specifically board gender diversity and board independence, on firm performance among the top 100 companies listed on Bursa Malaysia. Grounded in Agency Theory, this research explores how diverse board structures influence decision-making and firm outcomes. Agency Theory suggests that an effective board acts as a monitoring mechanism to align the interests of managers and shareholders, reducing agency costs and enhancing firm performance. Board gender diversity, in particular, contributes to stronger oversight, improved decision-making, and greater accountability. Using quantitative data extracted from the 2021 annual reports, the study analyzes the relationship between the number of female directors and independent directors with firm performance, measured by Return on Assets (ROA). The findings indicate a positive correlation between board gender diversity and firm performance, suggesting that greater female representation on boards strengthens governance effectiveness. However, board independence does not appear to have a significant effect on firm performance, possibly due to varying levels of engagement and expertise among independent directors. These results contribute to the ongoing discussion on corporate governance and firm success, offering insights for policymakers and stakeholders. Given that the percentage of female directors in Malaysia remains relatively stable, the findings may not fully capture the potential long-term effects of increased gender diversity. It is recommended that companies and regulatory bodies further promote gender equality by encouraging higher female participation in the workforce and increasing the representation of women on corporate boards to enhance governance effectiveness and mitigate agency conflicts